High-Altitude Cognitive Impairment Is Prevented by Enriched Environment Including Exercise via VEGF Signaling - Koester-Hegmann, Christina; Bengoetxea, Harkaitz; Kosenkov, Dmitry; Thiersch, Markus; Haider, Thomas; Gassmann, Max; Schneider Gasser, Edith M. (Frontiers in Cellular Neuroscience, 2019)
Exposure to hypobaric hypoxia at high altitude (above 2500 m asl) causes cognitive impairment, mostly attributed to changes in brain perfusion and consequently neuronal death. Enriched environment and voluntary exercise has been shown to improve cognitive function, to enhance brain microvasculature and neurogenesis, and to be neuroprotective. Here we show that high-altitude exposure (3540 m asl) of Long Evans rats during early adulthood (P48-P59) increases brain microvasculature and neurogenesis but impairs spatial and visual memory along with an increase in neuronal apoptosis. We tested whether enriched environment including a running wheel for voluntary exercise (EE) can prevent cognitive impairment at high-altitude and whether apoptosis is prevented. We found that EE retained spatial and visual memory at high altitude, and prevented neuronal apoptosis. Further, we tested whether vascular endothelial growth factor (VEGF) signaling is required for the EE-mediated recovery of spatial and visual memory and the reduction in apoptosis. Pharmacological inhibition of VEGF signaling by oral application of a tyrosine kinase inhibitor (Vandentanib) prevented the recovery of spatial and visual memory in animals housed in EE, along with an increase in apoptosis and a reduction in neurogenesis. Surprisingly, inhibition of VEGF signaling also caused impairment in spatial memory in EE-housed animals reared at low altitude, affecting mainly dentate gyrus microvasculature but not neurogenesis. We conclude that EE-mediated VEGF signaling is neuroprotective and essential for the maintenance of cognition and neurogenesis during high-altitude exposure, and for the maintenance of spatial memory at low altitude. Finally, our data also underlines the potential risk of cognitive impairment and disturbed high altitude adaption from the use of VEGF-signaling inhibitors for therapeutic purposes.